Passing the certified bariatric nurses exam - Loveitt, Andrew; Martin, Margaret M.; Neff, Marc (Springer, 2017)
The Certified Bariatric Nurse (CBN) designation was created by the American Society for Metabolic and Bariatric Surgery to fill the rapidly growing need for nurses specialized in the care of patients undergoing weight loss surgery. This book approaches this subject area to assist nurses interested in passing the CBN exam. It can also be used as a general resource for those interested in a comprehensive but concise review of the rapidly growing field of Bariatric Surgery. This would include medical students, residents, dietitians, and other allied health professionals. Dr. Marc Neff is a recognized expert in the field of Bariatric Surgery. In his current position, his hospital is fortunate to have several CBNs caring for the Bariatric patients. With his guidance, along with several nurses who successfully completed the CBN designation, the authors have created a concise, "quick hit" review of the material required to successfully pass the exam. The format is short chapters followed by 5-10 review questions with in-depth explanations. Where appropriate, graphics are provided to highlight the essential anatomy and surgical procedures. Questions are in multiple choice format to simulate the actual CBN exam.